The Influence of Customers' Favor of Saving at PT Bank Syariah Indonesia (BSI) Banda Aceh - Nasir; Sufyan (Divisi Riset, Lembaga Mitra Solusi Teknologi Informasi (L-MSTI), 2023)
Customers' habits of using savings products are considered important and can also be considered by PT's management. Bank Syariah, Indonesia (BSI), this also plays a very important role in efforts to build marketing policies for Sharia Bank's own savings products. This study aims to understand customer preferences for Bank Syariah Indonesia's savings products, including whether there are any differences in customer preferences for savings products based on characteristics. their points or not, as well as the attributes of savings products that most influence customers' decisions. Use savings products of this bank. The respondents were 65 customers of the Easy Mudarabah Savings product of the Banda Aceh branch of Bank Syariah Indonesia (BSI). Data collection was carried out by distributing questionnaires. The data were then analyzed using a non-parametric statistical device using the Mann-Whitney technique (U-Test). The research results show that the relationship between customers' preferences or interests in using Easy Mudarabah Savings products at BSI Banda Aceh branch includes economic benefits, banking location, safety of coins money, conformity to beliefs, concept of profit sharing, understanding of religion. mass media and customer environment. The customer's environmental factor is a factor that is given much priority over other indicators. Based on the results of statistical tests, it is known that differences in gender, age, marital status, and education level do not lead to differences in preferences for the three financial products, therefore Ho1, Ho2, Ho3 and Ho4 are accepted, while hypotheses Ha1, Ha2, Ha3 and Ha4 are rejected. On the other hand, differences in employment and average monthly income mean that customer preferences for financing products also vary. (Ha5, Ha6 are accepted and vice versa Ho5, Ho6 are rejected). The conclusions that can be drawn from this study are economic benefits, position of the bank, safety of money, compatibility with beliefs, concept of profit sharing, understanding of religion Education, mass media and customer environment are customer preferences in using savings products at Syariah Bank. Indonesia (BSI), among them, customers' environmental factors are the most dominant and preferred factors of customers compared to other factors.